When the inevitable surprises occur ... Are you ready to diffuse the situation with the right questions? - Fadem, Terry J.; Fadem, Terry J.; Safari eBooks (Upper Saddle River, N.J. : Pearson Education publishing as FTPress Delivers, 2010)
"This Element is an excerpt from 'The art of asking : Ask better questions, get better answers' by Terry Fadem. Ask the right questions to recover from any surprise and transform shocks into breakthroughs! Here's an effective, question-based strategy for handling surprise"--Resource description page.
Description based on resource description page (viewed Mar. 15, 2010).
"An e-burst of inspiration from the best books"--Cover.
Keywords: Communication in management; Executive ability; Organizational behavior; Electronic books